INFLUENCE OF ABIOTIC STRESS FACTORS ON BLACKCURRANT RESISTANCE TO PESTS (GEOMATE Journal, 2017)
Blackcurrant is one of the most valuable berries in a temperate zone. Lampronia capitalla Cl.is an extremely dangerous pest of blackcurrant in the South Ural region. Abiotic stress factors can significantly reduce blackcurrant resistance to L. capitella Cl. We studied blackcurrant in two areas and in a laboratory. The first area is situated close to a residential area, and a busy motorway is just 100 m from thisstation. The second area consists of 5 private household plots in an environmentally clean area, far from the city and motorways. We noted that, in the horticultural selection station, L. capitella Cl. population explosion was often three times more than in the household plots. We compared the growth of L. capitella Cl. larvae in nature and in the laboratory at different temperatures. The experiment lasted for 7 days at +25 °С in the laboratory, and for more than 13 days at daily average temperatures of +9.7 °… +15.1 °С in private household plots. We discovered that the larvae’s harmfulness increases at temperatures less than +25 °С.Under the influence of anthropogenic stress coefficient of assimilated food was higher than in clean areasbecause there is the low immunity of blackcurrant in adverse environmental conditions.